CHALLENGES AND OPPORTUNITIES OF ARTIFICIAL INTELLIGENCE INTEGRATION INTO NIGERIAN UNIVERSITY SYSTEM - Akindeyi Luwoye; Abiola Tawa Ahmed; Olasunkanmi Ibrahim Yusuf; Jimoh Akanbi Abdulraheem (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The integration of Artificial Intelligence (AI) into education systems worldwide is rapidly transforming traditional learning environments. However, the adaptation of AI technologies in developing countries, such as Nigeria, presents unique challenges and opportunities. This study explores the multifaceted influence of AI on the Nigerian education sector, examining both the barriers to successful implementation and the potential benefits. Challenges identified include inadequate infrastructure, limited internet connectivity, insufficient funding, lack of skilled personnel, and concerns over data privacy and security. Despite these obstacles, AI has the potential to revolutionize Nigerian education through personalized learning, improved administrative efficiency, enhanced content delivery, and data-driven decision-making. Collaboration, skill development, and ethical considerations also emerge as critical factors in maximizing AI's potential in Nigerian higher education. The study concludes that there is necessity for strategic investments in infrastructure, training programs, and a robust regulatory framework to harness AI's benefits while addressing its challenges. The study also concludes with policy recommendations and a roadmap for fostering sustainable AI-driven educational advancements in Nigeria.